Program Pengabdian Masyarakat Terpadu (PPMT) ‎ Pada UMKM Bolu Emprit dan Kue Es Di Dusun Krajan 2, Desa ‎Grabag Kabupaten Magelang - Wibowo, Septi; Swasono, Tutugo; Handarini, Ayudya Windhiasani; Dewi, Shylvia Ratna; Pandaya, Haris Aditya (Indra Institute Research & Publication, 2022)
The change in the marketing system from traditional to digital marketing to face the 5.0 era forced MSMEs to make changes in their product marketing system through social media and E-Commerce. Based on this, there are still many MSME actors who do not understand digital marketing. For this reason, the purpose of this ICSP activity is to provide knowledge and training for MSMEs about digital marketing for marketing by utilizing the marketplace and e-commerce. The method of ICSP activities is socialization, technology guidance and increasing production capacity directly to MSME actors. The object of ICSP is Bolu Emprit UD SMEs. Siti Mariyam in Krajan, Grabag Village, Grabag District, Magelang Regency who does not yet know the digital marketing system for marketing. The results of this ICSP are that MSME owners get additional knowledge and knowledge about digital marketing starting from the understanding, types, and uses for marketing MSME products and can increase production capacity by adding baking sheets.